Impact of temperature on Downs herring (Clupea harengus) embryonic stages: First insights from an experimental approach. - Lola Toomey; Carolina Giraldo; Christophe Loots; Kélig Mahé; Paul Marchal; Kirsteen MacKenzie (PLoS ONE, 2023)
Among all human-induced pressures, ocean warming is expected to be one of the major drivers of change in marine ecosystems. Fish species are particularly vulnerable during embryogenesis. Here, the impact of temperature was assessed on embryonic stages of Atlantic herring (Clupea harengus), a species of high socio-economic interest, with a particular focus on the under-studied eastern English Channel winter-spawning component (Downs herring). Key traits linked to growth and development were experimentally evaluated at three temperatures (8°C, 10°C and 14°C), from fertilization to hatching, in standardized controlled conditions. Overall negative impacts of increased temperature were observed on fertilization rate, mean egg diameter at eyed stage, hatching rate and yolk sac volume. A faster developmental rate and a change in development stage frequency of newly hatched larvae were also observed at higher temperature. Potential parental effects were detected for four key traits (i.e. fertilization rate, eyed survival rate, mean egg diameter and hatching rate), despite a limited number of families. For instance, a large variability among families was shown in survival rate at eyed stage (between 0 and 63%). Potential relationships between maternal characteristics and embryo traits were therefore explored. We show that a substantial proportion of variance (between 31 and 70%) could be explained by the female attributes considered. More particularly, age, traits linked to life history (i.e. asymptotic average length and Brody growth rate coefficient), condition and length were important predictors of embryonic key traits. Overall, this study constitutes a stepping-stone to investigate potential consequences of warming on Downs herring recruitment and provides first insights on potential parental effects.